Marriage Practices Through Wild Qadhi According to Langsa City Ulema from the Perspective of Maqasid Syariah - Muhammad Husni (Tunas Institute, 2023)
This study aims to find out what are the factors that occur i n the practice of illegal Qadhi and to find out how the perspective of the Ulama Consultative Council (MPU) on the practice of illegal Qadhi. This study uses empirical juridical research methods. The author uses a legal awareness approach with a qualitative research type, where the author collects research data sources from interviewees, observations, pictures and documents. The results show that what causes the practice of illegal Qadhi in the community are: First, economic factors where in addition to illegal Qadhi actors who need additional income, married couples are also due to their lack of economy or finances. Second, the age factor where the perpetrators of illegal qadhi marry to help underage couples. Third, there is no guardian factor that makes couples who want to get married prefer to be married by illegal Qadhi. Fourth, the pregnancy factor. Fifth, the polygamy factor. Based on the results of the author's interview with MPU Kota Langsa, MPU's own view, says that marriages that occur through illegal Qadhi are not valid. when one performs a marriage through illegal Qadhi this is considered to be a veiled adultery. Based on the results of the interview, MPU is of the opinion that why marriages through illegal Qadhi are considered invalid because what must be understood is that the conditions for a valid marriage must have a guardian.